Rapid phase-controlled microwave synthesis of nanostructured hierarchical tetragonal and cubic beta-In2S3 dandelion flowers - Naik, S. D.; Jagadale, Tushar C.; Apte, S. K.; Sonawane, S.; Kulkarni, M. V.; Patil, S. I.; Ogale, Satishchandra B.; Kale, B. B. (Chemical Physics Letters, 2008)
Phase controlled synthesis of hierarchical nanostructured beta-In2S3 dandelion flowers is realized by a rapid microwave solvothermal process using indium metal, nitric acid and thiourea as precursors. The tetragonal and cubic phases of the compound have been successfully and separately stabilized in the same type of dandelion morphology by using aqueous-mediated and methanol-mediated synthesis, respectively. The possible mechanism responsible for phase control is discussed. Optical properties of the flowers as well as their hydrogen generation capability by photodecomposition of H2S under visible light are also reported. (c) 2007 Elsevier B.V. All rights reserved.

Controlling stoichiometry in low temperature synthesis of La0.7Sr0.3MnO3 nanoparticles - Azarifar, Ali; Yadav, P. A.; Chawla, A. K.; Jog, Jyoti Prakash; Patil, S. I.; Chandra, Ramesh; Ogale, S. B. (Advanced Science Letters, 2011)
Nanoparticles of complex oxides (<20 nm) are desirable for several applications in view of the diverse range of physical properties of such oxides. However the simultaneous presence of multiple cation precursors makes the corresponding chemical synthesis non-trivial with possible intermediate evolution of secondary phases. Such phases could react at high temperatures to form the desired stoichiometry, but this process is diffusion limited and can lead to larger particles. In this work we examine the role of three different reaction and growth controlling additives, namely dextran, citric acid and hexamine, on the synthesis of the well known colossal magneto-resistive (CMR) manganite La0.7Sr0.3MnO3. We demonstrate that phase evolutions differ significantly in the three cases, and the physical properties of the products also differ dramatically. Only dextran is shown to yield the desired phase with faceted nanoparticles at as low a temperature as 600 degrees C. A high saturation moment of similar to 47 emu/gm is realized at 10 K with a good square hysteresis loop. In 650 degrees C annealed sample, room temperature magnetization of similar to 15 emu/gm was obtained, which brings the nanoparticles in the applicability domain.
Keywords: Citric acid; Complex Oxide; Dextran; Hexamine; hydrothermal